Assessing the impact of a cathedral pre-Christmas son et lumiere on participants’ psychological wellbeing and spiritual health - Francis, Leslie J. (Journal of beliefs and values, 2025)
This study employs The Index of Balanced Affect Change (TIBACh) and the Francis Index of Spiritual Health Change (FISH) to assess the perceived impact on 518 participants who attended the Starlight pre-Christmas son et lumiere in Liverpool Cathedral. The Index of Positive Affect Change demonstrated that up to two-thirds of the participants went away feeling more positive about life. The Index of Existential Spiritual Health Change demonstrated that around two-fifths went away feeling more positive about relationships with themselves, with others, and with the world. The greater impact on existential spiritual health was among younger people. The greater impact on psychological wellbeing was among those without connections with a religious worldview. In other words, the installation is enabling the cathedral to extend the Church’s reach among the young and among the unchurched.